JCMR 2021
DOI: 10.46889/jcmr.2021.2202
|View full text |Cite
|
Sign up to set email alerts
|

Screening Pilot Study of Fruit Seed Compositions by GC-MS and Their Potential Scenario Anti ACE2 and 2rh1 Receptors as a Recycling Possibility in the Coronavirus Pandemic

Abstract: Background: Since 2019, several critical effects of the coronavirus pandemic have surfaced, including its psychological problems such as depression. The World Health Organization has approved a group of drugs and vaccines. However, the world still faces novel coronavirus mutations, requiring more ideas to investigate a drug, vaccine and phytochemical potential chemoprevention proposal. Severe Acute Respiratory Syndrome-Coronavirus (SARS-CoV)-2 co-operates directly with the Angiotensin-Converting Enzyme 2 (ACE2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 66 publications
(89 reference statements)
1
7
0
Order By: Relevance
“…The results showed an improvement in the rats’ skin levels of collagenase, elastase, hyaluronidase, tyrosinase, nitric oxide (NO), malondialdehyde (MDA), and cyclooxygenase2 (COX-2) following PSOE treatment against phenobarbital and formaldehyde, with no effects in the group treated with PSOE alone. This agreed with our previous finding, where we observed no side effects on the biological profiles, including the liver and kidney profiles, DNA fragmentation, and histopathological markers at doses under 250 mL/kg following short- and long-term treatment with pomegranate seed oil extract [ 18 , 20 , 21 , 22 ]. Additionally, the results showed that the biochemical parameters in the humans were significantly ameliorated with PSOE treatment, compared with those in Group 1.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…The results showed an improvement in the rats’ skin levels of collagenase, elastase, hyaluronidase, tyrosinase, nitric oxide (NO), malondialdehyde (MDA), and cyclooxygenase2 (COX-2) following PSOE treatment against phenobarbital and formaldehyde, with no effects in the group treated with PSOE alone. This agreed with our previous finding, where we observed no side effects on the biological profiles, including the liver and kidney profiles, DNA fragmentation, and histopathological markers at doses under 250 mL/kg following short- and long-term treatment with pomegranate seed oil extract [ 18 , 20 , 21 , 22 ]. Additionally, the results showed that the biochemical parameters in the humans were significantly ameliorated with PSOE treatment, compared with those in Group 1.…”
Section: Discussionsupporting
confidence: 93%
“…Additionally, these elements support both the immune and endocrine systems against opportunistic bacteria and fungi [ 1 , 51 , 53 ]. In both our past work and current studies, we found that pomegranate contains phytochemicals, including squalene, gamma-tocopherol, cis-11-eicosenamide, hexadecanamide, hydroxymethylfurfural, stigmastan-3,5-diene, oleamide, pentanoic acid, and octadecanoic acid, which have antiapoptotic, anti-inflammatory, antioxidant, antibacterial, and antifungal activities ( Table 2 ) [ 22 , 23 , 54 ]. Additionally, our previous findings indicated that the active phytochemicals in pomegranate could be used in schizophrenia and depression treatment, as a sedative agent, and to treat neurological stress through the downregulation of epinephrine, cortisol, and inflammatory cytokine receptors, in agreement with our current findings [ 22 , 23 , 54 ].…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations